MODELS OF IMPROVING THE QUALITY OF HIGHER EDUCATION - Jo‘rayev Soxibjon Nodirbek o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The socio-economic importance and cultural aspects of the concept of higher education quality are analyzed in the article. Various scientific approaches to rating the quality of education have been described. Different national systems of ensuring the quality of education in practice in the world are compared. Internal and external evaluation mechanism of higher education quality improvement models is analyzed. Models of quality assurance of higher education and the effectiveness of their use have been determined in world practice. In particular, the international reputation of the French model, the English model and the Bologna model and the possibilities of using these models are revealed. A scientific proposal and practical recommendations have been developed for the implementation of international requirements and recommendations aimed at ensuring the quality of higher education in Uzbekistan.